Simultaneous Detection of Mycobacterium leprae and Its Susceptibility to Dapsone Using DNA Heteroduplex Analysis - Williams, Diana L. (American Society for Microbiology, 2001)
Currently recommended control measures for treating leprosy with multidrug therapy should control the spread of drug-resistant strains; however, dapsone (DDS) resistance continues to be reported. Comprehensive estimates of drug-resistant leprosy are difficult to obtain due to the cumbersome nature of the conventional drug susceptibility testing method using mouse footpad inoculation, which requires at least 6 months to obtain results. Recently, it has been determined that DDS-resistant strains contain missense mutations in codon 53 or 55 of the folP1 gene of Mycobacterium leprae, and definitive evidence linking these mutations with DDS resistance in M. leprae has been obtained. Based on these mutations, a heteroduplex DDS M. leprae (HD-DDS-ML) assay was developed for the simultaneous detection of M. leprae and of its susceptibility to DDS. The assay relies on the PCR amplification of an M. leprae-specific 231-bp fragment of folP1 containing codons 53 and 55. The PCR products are allowed to anneal to a universal heteroduplex generator, and the separation of the resultant DNA duplexes is accomplished by polyacrylamide gel electrophoresis. M. leprae was detected in crude cell lysates of skin biopsy specimen homogenates from eight leprosy patients and from M. leprae-infected mouse or armadillo tissues infected with 14 separate strains using the HD-DDS-ML assay. The assay was specific for M. leprae in a comparison with results obtained from 14 species of mycobacteria other than M. leprae and four bacterial species known to colonize human skin. The HD-DDS-ML assay detected as few as 100 M. leprae organisms present in homogenates of human skin and demonstrated a 93% correlation with DDS susceptibility as determined by both DNA sequencing of folP1 and mouse footpad susceptibility testing. The HD-DDS-ML assay provides a new tool for the simultaneous detection of M. leprae and of its susceptibility to DDS from a single specimen. The assay should prove useful for drug resistance surveillance in leprosy control programs when combined with similar molecular tests developed for other drug resistance markers.